Isolation of Lactic Acid Bacteria from Intestines of Eel (Monopterus albus) Raised in Biofloc System Cultivation - Feri Julianto; Iesje Lukistyowati; Henni Syawal (Jurusan Budidaya Perairan, Fakultas Perikanan dan Kelautan, Universitas Riau, 2023)
Biofloc technology is one of the most profitable alternative solutions to the problem of aquaculture waste. The research was carried out from July to August 2020 at the Laboratory of Fish Parasites and Diseases, Faculty of Fisheries and Marine Affairs, Riau University. The purpose of this study was to isolate and identify candidate lactic acid bacteria (LAB) that have the potential as probiotics from the intestines Monopterus albus and to determine the growth rate of candidate probiotic bacteria and can suppress the growth of the pathogenic bacteria Aeromonas hydrophila. The method used is the experimental method with treatment of pH 2, pH 4 and pH 6, isolation was carried out from the best Monopterus albus rearing with a stocking density of 30 fish/25 liters of water. Candidate probiotic bacteria was found from the intestines of Monopterus albus as many as 6 LAB candidate isolates based on the results of physical, biochemical and pH treatments, the morphology of the probiotic candidate isolates consisted of one type of bacteria, namely Lactobacillus, from the 6 isolates which showed the widest zone of inhibition against the pathogenic bacteria Aeromonas hydropila was isolate derived from Monopterus albus intestine result shown that which grows at pH 2 is BL 2.1.1 with an inhibition zone diameter of 9,05 mm.